Crash course in EPaCCS (Electronic Palliative Care Coordination Systems): 8 years of successes and failures in patient data sharing to learn from - Petrova, Mila (BMJ Support Palliat Care, 2018)
BACKGROUND: Electronic Palliative Care Coordination Systems (EPaCCS) are England's pre-eminent initiative in enabling advance care planning and improved communication and coordination at the end of life. EPaCCS have been under development for 8 years after being proposed, as Locality Registers, in the 2008 End of Life Care Strategy for England. EPaCCS are electronic registers or tools and processes for sharing data which aim to enable access to information about dying patients. Striking outcomes have been reported around EPaCCS, such as 77.8% of ‘Coordinate My Care’ patients dying in their preferred place. EPaCCS have, however, been extremely challenging to develop and implement, with many projects remaining continuously ‘under development’ or folding. They also continue to be suboptimally integrated with other data sharing initiatives. Rigorous research is non-existent. DISCUSSION POINTS: We discuss the current EPaCCS landscape and way forward. We summarise key facts concerning the availability, uptake, outcomes and costs of EPaCCS. We outline 5 key challenges (scope of projects, unrealistic expectations set by existing guidance, the discrepancy between IT realities in healthcare and our broader lives, information governance and ‘death register’ associations) and 6 key drivers (robust concept, striking outcomes, national support and strong clinical leadership, clinician commitment, education and funding). CONCLUSIONS: The priorities for advancing EPaCCS we propose include linking to other work streams and reframing the concept, potentially making it less ‘end of life’, overview of current EPaCCS and lessons learnt, continuing work on information standards, rethinking of national funding and new levels of individual and community involvement.